Melatonin Prevents Alcohol- and Metabolic Dysfunction- Associated Steatotic Liver Disease by Mitigating Gut Dysbiosis, Intestinal Barrier Dysfunction, and Endotoxemia - Karli R. LeFort; Wiramon Rungratanawanich; Byoung-Joon Song (Antioxidants, 2023)
Melatonin (MT) has often been used to support good sleep quality, especially during the COVID-19 pandemic, as many have suffered from stress-related disrupted sleep patterns. It is less known that MT is an antioxidant, anti-inflammatory compound, and modulator of gut barrier dysfunction, which plays a significant role in many disease states. Furthermore, MT is produced at 400–500 times greater concentrations in intestinal enterochromaffin cells, supporting the role of MT in maintaining the functions of the intestines and gut–organ axes. Given this information, the focus of this article is to review the functions of MT and the molecular mechanisms by which it prevents alcohol-associated liver disease (ALD) and metabolic dysfunction-associated steatotic liver disease (MASLD), including its metabolism and interactions with mitochondria to exert its antioxidant and anti-inflammatory activities in the gut–liver axis. We detail various mechanisms by which MT acts as an antioxidant, anti-inflammatory compound, and modulator of intestinal barrier function to prevent the progression of ALD and MASLD via the gut–liver axis, with a focus on how these conditions are modeled in animal studies. Using the mechanisms of MT prevention and animal studies described, we suggest behavioral modifications and several exogenous sources of MT, including food and supplements. Further clinical research should be performed to develop the field of MT in preventing the progression of liver diseases via the gut–liver axis, so we mention a few considerations regarding MT supplementation in the context of clinical trials in order to advance this field of research.